Impact and Role of Marketplace and Financial Literacy on Financial Control - Selsa Mada Pramudia Wardani; Ratri Cahyaning Asri; Cecilia Arthur Limantara; Dika Antoni Putra; Tyo Riyandi; Agus Dwi Sasono (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to create a reference model for the national Financial Literacy movement by finding a Financial Control model for Generation Z of Surabaya, which is 0.03% of the total in Indonesia. Therefore, the researchers made it the subject of research. Design/methodology/approach: In determining the minimum number of samples, the researcher used the Slovin formula. The research instrument used was a questionnaire. Findings: The study results show that the model relates to the Marketplace and financial literacy. Here, Marketplace has a significant impact and weak influence on Financial Control. At the same time, Financial Literacy has a substantial and robust effect on Financial Control. While Marketplace on Financial Control through Financial Literacy has a significant impact and a reasonably vital influence role. The findings are that 53% of research subjects think the literacy movement with animated video models through digital media is more attractive than others. Originality/value: This paper is original Paper type: Research article